2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1616055
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Tongue Diagnosis System

Abstract: To circumvent the subjective and qualitative problems of traditional tongue diagnosis, we present a novel computer aided tongue diagnosis system (CATDS). In this system, a standard acquisition device as well as a new color correction method is utilized to capture qualified tongue images. The system is constituted by five components: User Interface Module, Acquisition Module, Tongue Image Database, Image Preprocessing Module and Diagnosis Engine. In contrast to existing CATDS, the proposed system aims to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 4 publications
0
48
0
Order By: Relevance
“…Generally, the proposed method can well address the edge enhancement and the contour discontinuity problems. Experimental results also showed that the proposed method is more effective than other tongue body segmentation methods, i.e., BEDC [35], Watershed [36], and PolarSnake [32].…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Generally, the proposed method can well address the edge enhancement and the contour discontinuity problems. Experimental results also showed that the proposed method is more effective than other tongue body segmentation methods, i.e., BEDC [35], Watershed [36], and PolarSnake [32].…”
Section: Resultsmentioning
confidence: 68%
“…We further compared the proposed GaborFM method with three other tongue body segmentation methods: BEDC [35], Watershed [36], and PolarSnake [32]. Figure 10 shows the segmentation results of three typical tongue images obtained using the four segmentation methods: BEDC [35], Watershed [36], PolarSnake [32], and GaborFM.…”
Section: Comparison With the Other Segmentation Methodsmentioning
confidence: 99%
See 3 more Smart Citations